Research Trends of Implementation E-Learning in Engineering Education: A Bibliometric Analysis and Policy Implications - Anwar, Syairi; Suhanto; Bambang Bagus Hariyanto; Irfan (Universitas Pendidikan Ganesha, 2025)
The digital transformation of technical education in developing countries is hampered by infrastructure limitations, access gaps, and the low effectiveness of e-learning, especially in virtual laboratories.This study aims to analyze and map global research trends on e-learning implementation in engineering education using bibliometric methods to provide comprehensive insights into its development and policy implications. A total of 288 articles published between 2013 and 2023 were collected from the Scopus database and analyzed through a quantitative bibliometric approach. The data were processed using VOSviewer software to visualize publication trends, keyword co-occurrence networks, and thematic research clusters. The results reveal a significant increase in publications and citations over the past decade, notably accelerated during the COVID-19 pandemic. The co-occurrence analysis identified four dominant research themes: learning effectiveness, educational digitalization, adaptive technologies, and digital transformation in engineering education. Notably, the integration of Artificial Intelligence (AI) and Virtual/Augmented Reality (VR/AR) technologies has enhanced student engagement, virtual practicums, and teaching effectiveness. However, substantial geographical disparities and infrastructure gaps remain major barriers in many regions. These findings emphasize the need for comprehensive education policies that include strengthening digital infrastructure, improving teaching quality, learning management, and equal access. Recommendations include international collaboration and adaptive strategies to realize effective and sustainable technical e-learning.